2019
DOI: 10.1021/acsbiomaterials.9b00658
|View full text |Cite
|
Sign up to set email alerts
|

Sustained Intracellular Raltegravir Depots Generated with Prodrugs Designed for Nanoparticle Delivery

Abstract: Polymeric nanocarriers have been extensively used to improve the delivery of hydrophobic drugs, but often provide low encapsulation efficiency and percent loading for hydrophilic compounds. In particular, insufficient loading of hydrophilic antiretroviral drugs such as the integrase inhibitor raltegravir (RAL) has limited the development of sustained-release therapeutics or prevention strategies against HIV. To address this, we developed a generalizable prodrug strategy using RAL as a model where loading, rele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…ESI tandem MS has been used more extensively than MALDI-MS/MS in the analysis of biodegradable polymers. In the literature, ESI-MS/MS studies concern fragmentation analysis and insights on comparative dissociation tools [ 50 , 51 , 53 , 55 , 82 ], structural characterization [ 19 , 55 , 63 , 64 , 65 , 67 , 68 , 70 , 71 , 72 , 74 , 75 , 80 , 81 , 83 , 86 , 121 , 122 , 123 , 124 , 125 , 126 ], drug delivery systems [ 89 , 90 , 91 , 95 , 96 , 97 , 98 , 100 , 101 , 102 , 103 , 104 , 105 , 106 , 107 , 108 , 109 , 110 , 111 , 112 ] and degradation studies [ 111 , 112 , 113 , 114 , 115 , …”
Section: Esi Tandem Mass Spectrometry Studiesmentioning
confidence: 99%
See 2 more Smart Citations
“…ESI tandem MS has been used more extensively than MALDI-MS/MS in the analysis of biodegradable polymers. In the literature, ESI-MS/MS studies concern fragmentation analysis and insights on comparative dissociation tools [ 50 , 51 , 53 , 55 , 82 ], structural characterization [ 19 , 55 , 63 , 64 , 65 , 67 , 68 , 70 , 71 , 72 , 74 , 75 , 80 , 81 , 83 , 86 , 121 , 122 , 123 , 124 , 125 , 126 ], drug delivery systems [ 89 , 90 , 91 , 95 , 96 , 97 , 98 , 100 , 101 , 102 , 103 , 104 , 105 , 106 , 107 , 108 , 109 , 110 , 111 , 112 ] and degradation studies [ 111 , 112 , 113 , 114 , 115 , …”
Section: Esi Tandem Mass Spectrometry Studiesmentioning
confidence: 99%
“…Chromatographic separation combined with tandem MS has been more and more recurrently used in the assessment of biodegradable DDS, such as microspheres, micelles, or nanoparticles, measuring drug loading or concentration [ 97 , 100 , 101 , 102 , 103 , 104 , 105 , 106 , 107 , 108 , 109 , 111 , 112 ] and monitoring drugs or hormone release, in vitro and in vivo [ 89 , 90 , 91 , 95 , 96 , 102 , 110 , 111 ]. Recently, Ultra-HPLC (UHPLC) with MS/MS methods has been developed, attracting considerable interest in pharmacokinetic studies for its high sensitivity, accuracy, and precision.…”
Section: Esi Tandem Mass Spectrometry Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar results were obtained using a 5′- O -myristoyl conjugate of 3TC where a long-acting nanoformulation of a fatty acyl conjugate of 3TC was shown to reduce hepatitis B virus replication in humanized mice [ 23 ]. Additionally, Creighton et al demonstrated that fatty acid conjugation with raltegravir tuned its release pattern, hydrolysis rate, and anti-HIV activity [ 24 ]. Overall, the studies revealed that the prodrug action was dependent on the type of conjugated fatty acid and the position of the conjugation of fatty acid to the drug.…”
Section: Introductionmentioning
confidence: 99%
“…However, the high water-solubility makes platinum hard to be encapsulated into nanoparticles efficiently (Ita, 2016 ; Arduino et al., 2020 ). Thus, the chemical conjugate based prodrug (Gu et al., 2019 ) is confirmed to be one of the most potential routes to improve the poor therapeutic effect of platinum, and now become a hot area of research (Feazell et al., 2007 ; Rieter, et al., 2008 ; Dhar et al., 2011 ; Li et al., 2012 ; Butler & Sadler, 2013 ; Kumar et al., 2014 ; Creighton et al., 2019 ). This is because that the prodrug platinum (IV) complexes usually have low spin d 6 selective configuration and octahedral geometry (Li et al., 2018 ; Liu et al., 2019 ; Chen et al., 2020 ), which endow them with high kinetic inertia to substitution (Graf & Lippard, 2012 ).…”
Section: Introductionmentioning
confidence: 99%